Inventory of scientific publications on urban forestry published between 1800 and 2015: An analysis by period, topic and origin - Jacques Larouche; Danny Rioux; Adrina C. Bardekjian; Nancy Gélinas (The Forestry Chronicle)
Research in urban forestry (UF) is rapidly evolving. In order to better understand this increased interest among the scientific community, a comprehensive inventory of scientific articles published between 1800 and 2015 on the subject was carried out. To do so, 21 keywords were used to query six different databases. Data was gathered and analyzed using the Endnote x7 reference management software. Some 3100 papers were identified and grouped by period, topic and author origin. The results show that the number of papers published has constantly risen since 1800, more so over the last decades. For example, the number of papers more than doubled between 2000 and 2009 compared to the previous decade (1990–1999). If this trend continues, the number of publications could double again between 2010 and 2019. This observation is valid for all countries, except for Scandinavian and Baltic countries where the number of related articles has decreased in recent years. The most commonly studied topics are human health and sociology, followed by air quality and pollutants. These results show, among other things, that UF research is thriving and that many scientists appear particularly preoccupied by the impacts of global warming.